Association of Anger Expression-Out with NK Cell Counts in Colorectal Cancer Patients - Kakoo-Brioso, Estela (2018)
Introduction: There is growing evidence describing the relation between psychological factors and the progression of colorectal cancer. Several mechanisms have been proposed but the one showing more promising evidence relies on the modulation of the antitumoral immune response by psychological factors, particularly through natural killer cells. We aimed to study the relation between natural killer cell count and anxiety, depression and anger state, trait and expression in 54 pre-surgical colorectal cancer patients.Material and Methods: We measured peripheral blood natural killer cell count and applied the State-Trait Anger Expression Inventory and the Hospital Anxiety and Depression Scale to 54 pre-surgical colorectal cancer patients. We used the Mann-Whitney U test and the Kruskal-Wallis test when appropriate to compare independent groups.Results: Patients with higher Anger Expression-Out had lower natural killer cell numbers than patients with lower Anger Expression-Out (p value = 0.008). No relation was found between natural killer cell levels and Anger State, Anger Trait, or Anger Expression-In. No difference in natural killer cell count was found between patients with and without clinical anxiety or depression.Discussion: These results suggest that, in colorectal cancer patients, natural killer cell counts are influenced by Anger Expression-Out, but not by clinical anxiety or depression.Conclusion: The unregulated emotional expression might be a conditioning factor of innate immunity. Additional studies are needed to further investigate this relation and to ascertain the clinical impact of therapeutic interventions regarding emotional regulation on the anti-tumoral immune response.